Contribution of the Umayyad Dynasty to the Development of Islamic Civilization (661-750 AD) - Zein, Nashrurrahman (Universitas Islam Negeri Raden Intan Lampung, 2022)
The Umayyah dynasty was a classical Islamic era government which was often seen as weak when compared to the Khulafaurrasyidin and Abbasid dynasty. This is partly due to the negative image that has developed among historians, especially as a result of the political developments that occurred at that time. Three things were seen as